Anda di halaman 1dari 2

) (

:
f ]_ [ !a, b F f ]_ [ !a, b
f a b :
b b
) a f ( x )dx = F ( x )a = F ( b ) - F ( a
:
:
a b a
b f ( x )dx = - a f ( x )dx a f ( x )dx = 0
b b b b b
a
f ( x ) + g ( x )
dx = a f ( x )dx + a g ( x )dx ) (k a kf ( x )dx = k a f ( x )dx
:
b c b
a f ( x )dx = a f ( x )dx + c f ( x )dx
:
] "x [ a, b f ( x ) g ( x ) : ] "x [ a, b f ( x ) 0 :
b b b
a f ( x )dx a g ( x )dx : a f ( x )dx 0 :
:
f ][a,b
1 b
] [ a,b f ( x )dx :
b-a a
:
[ #a, b ' f' g ] f g
] [ #a, b
b b
a
f ' ( x ) g ( x )
dx =
f ( x ) g ( x )
) ( a a
b
- f x g ' ( x ) dx

:
rr
( )
o,i, j
u . A :
r r
o i j
r r
1.u . A = i j

22
g ][a;b f f ][a;b
Cf Cf
Cg :
x = a y = b:
x = a : y = b:
b
b
a f ( x ) - g ( x ) dx

.u.A a f ( x ) dx .u.A

b f
a f ( x )dx .u.A ][a,b

b f
a -f ( x )dx .u.A ][a,b

f
c b ][a,c
a f ( x )dx + c -f ( x )dx .u.A f

][c, b

b ) ( Cf ) ( Cg
a ( f ( x ) - g ( x ) )dx .u.A
][a,b
) ( Cf ) ( Cg
c b
a ( f ( x ) - g ( x ) )dx + c ( g ( x ) - f ( x ) )dx .u.A ][a,c

) ( Cg ) ( Cf
][c, b
:
( Cf )
][a,b
b
V = p ( f ( x ) ) dx u.v :
a

23